OXTR Gene mRNA Expression is Correlated to Prosocial Behavior of Children in the Golden Generation Program of Nusa Tenggara Barat - Wilya Isnaeni; Suryani As'ad; Mochammad Hatta; Saidah Syamsuddin; Fahrin Ramadan Andiwijaya; Hamsu Kadriyan (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Cases of undernutrition, such as stunting and wasting, in Nusa Tenggara Barat (NTB), Indonesia, was found to be relatively high. Therefore, local government launched a golden generation program called GEN NTB to improve the quality of human resources by achieving a healthy, intelligent, devout, and productive generation in 2045. One of the genes known to be related with prosocial behavior is the oxytocin transferase (OXTR) gene. This study was conducted to determine the association between OXTR gene mRNA expression and prosocial behavior of the GEN NTB children.METHODS: This was an analytical observational case-control study involving 25 children as GEN NTB samples and 26 children as controls. Blood samples were tested for OXTR protein level with enzyme-linked immunosorbent assay (ELISA), and OXTR mRNA expression with real time polymerase chain reaction (RT-PCR). Prosocial behavior was characterized and determined by using a rating method, which valued from 1 to 4 for poor to very good behavior.RESULTS: The average OXTR protein levels of the GEN NTB group was 88.28 ng/mL, which were higher than the average OXTR protein levels of control group (2.41 ng/mL). According to fold change analysis, the OXTR mRNA expression in GEN NTB group was also higher than the control group (10.91 vs. 6.40). Interestingly, observations on the prosocial behavior of the GEN NTB group showed significantly higher rate values compared to the control group (17.3 vs. 8.0, p=0.034). Hence, these findings showed that the OXTR protein level and OXTR mRNA expression was correlated with the better prosocial behavior.CONCLUSION: Higher rating of prosocial behavior of the GEN NTB children is related to the higher OXTR mRNA expression levels. This might be attributed to the interventions of GEN NTB program that may elevate children's quality of life since early childhood.KEYWORDS: GEN NTB, OXTR protein, mRNA expression, prosocial behavior, children